The NLRP3 Inflammasome and Its Role in T1DM - Sun, Xiaoxiao; Pang, Haipeng; Li, Jiaqi; Luo, Shuoming; Huang, Gan; Li, Xia; Xie, Zhiguo; Zhou, Zhiguang (Frontiers in Immunology, 2020)
The NLRP3 (nucleotide-binding and oligomerization domain-like receptor family pyrin domain-containing 3) inflammasome is a protein complex expressed in cells. It detects danger signals and induces the production of active caspase-1 and the maturation and release of IL (interleukin)-33, IL-18, IL-1β and other cytokines. T1DM (type 1 diabetes mellitus) is defined as a chronic autoimmune disorder characterized by the autoreactive T cell-mediated elimination of insulin-positive pancreatic beta-cells. Although the exact underlying mechanisms are obscure, researchers have proposed that both environmental and genetic factors are involved in the pathogenesis of T1DM. Furthermore, immune responses, including innate and adaptive immunity, play an important role in this process. Recently, the NLRP3 inflammasome, a critical component of innate immunity, was reported to be associated with T1DM. Here, we review the assembly and function of the NLRP3 inflammasome. In addition, the activation and regulatory mechanisms that enhance or attenuate NLRP3 inflammasome activation are discussed. Finally, we focus on the relationship between the NLRP3 inflammasome and T1DM, as well as its potential value for clinical use.